Indonesian Vowels And Their Allophones - I Dewa Putu Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2003)
Verhar's books entitled Pengantar Linguistik (Introduction to Linguistics) published by Gadjah Mada University Press and its elaborative edition Asas-asas Linguistik (The Principles of Linguistics) of the same publisher constitute linguistic works which strongly influence the development and advancement of linguistic studies in Indonesia. The innovations brought by these books are clearly seen in their formal approach towards linguistic units as the material object of any linguistic investigation. Long before the appearance of those Verhar's books, Indonesian Linguists or linguists of bahasa Indonesia had been shackled by the traditional (notional) approach, as shown in the works of Alisjahbana (1978); Mees (1955); Zain (1943); Lubis (1954) (see Ramlan, 1985). Their traditional approach is a reflection of the strong influence of Greece grammar. Meanwhile, the formal approach practised by the modern linguists, in many respects, is much more objective than that of the traditional one. The modern approach is used, for examples, to identify linguistic units (such as morphemes, words, sentences, etc.), parts of speech, syntactic functions and their fillers, sentence types, etc. Despite those advantages, Verhaar's works also conceal various linguistic problems which are either related to Indonesian, foreign or local languages in Indonesia. The problems presented in those books are very interesting, and frequently challenging for linguists to think of or give them some corrections or solutions. The superiority of these books has been discussed by Alif (2002) in a regional conference held by University of Sanata Dharma, Yogyakarta to commemorate the one hundredth day of the author's death. Accordingly, as a token of my respect to his service in developing Indonesian linguistics and his dedication to Gadjah Mada University, where he was formerly a visiting professor in Faculty of Letters (now Faculty of Cultural Sciences), I would like to discuss one important problem which exists in his second book Asas-asas Linguistik. The problem concerns with Indonesian vowels and their allophonic distribution, especially / i/ and /u/ in Indonesian syllabic systems. These problems have not been so far satisfactorily clarified in Indonesian phonology.